Mysteries, vitrages and landscapes of Hennady Liashenko’s choral creation - Halas, Olesia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
The relevance of the study is determined by the insufficient attention of musicologists to the choral creative legacy of G. Lyashenko, which occupies one of the most important places in his creative biography, despite the fact that these pieces are the composer’s only recourse to the choral genre. Cantatas for the acapello chorus: T. Shevchenko’s ("Mystery of Silence") and B.-I. Antonich’s ("Vitrages and landscapes”) that appeared at the turn of the 2000sf immediately literally "burst" into the cultural space, having received two well-deserved awards - the most prominent Music Award in Ukraine and, more importantly, the attention and love of performers and listeners, thus becoming a notable phenomenon of modern Ukrainian choral music. The main objective of the study is to analyze the choral scores of cantatas in the aspect of musical sound pattern. Methodology. Methods of structural analysis of timbre dramaturgy, as well as expressive features and formative means of the composer’s choral ( acapello) writing, are involved. Results and conclusions. Analysis of choral cantatas by G. Lyashenko shows that the author, basing on the foundations of traditional choral writing, enriches it with the attributes of his musical language, in particular, through the methods of working with instrumental music, where he actively uses the elements of aleatory, sonority, polyharmony, and harmonic modality. An invariable sign of his style is polyphonic thinking. By polyphonic techniques - imitations, canons and all kinds of sub-voices - the composer, on the one hand, complicates the musical texture, and on the other hand, makes the musical roll-out of the constructions more clear. Without absolutizing any of the techniques, the composer in choral cantatas creates a very peculiar, albeit acapello-like, however colorful musical sound pattern. The practical significance. The use of acapello in modern music requires the understanding of the choir as a flexible, but to a certain extent limited "instrument," with which it is not so easy to achieve the purely sound colorful and expressive effects, that are available in instrumental music. And in this sense, G. Lyashenko’s choral cantatas are the vivid example of the usage of the modern techniques of choral writing.